2021
DOI: 10.1093/esr/jcaa056
|View full text |Cite
|
Sign up to set email alerts
|

Trends in Women’s Relative Earnings Within Couples Across the Transition to Parenthood in Sweden, 1987–2007

Abstract: This article applies a couple perspective to assessing gender inequality in Sweden—a setting with high maternal labour force participation, a long history of family policy investment, and strong norms of gender equality. We address open questions about how couples’ earnings following parenthood have changed over time, and how patterns of inequality in couples’ earnings have played out across educational groups. Our study uses fixed effects methods and register data covering the total population of heterosexual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 60 publications
0
28
0
Order By: Relevance
“…Even though the gap between women's and men's employment in general has decreased in Austria and women indeed increasingly participate in the labor market (Schmidt et al 2020), this country is characterized by high and growing part-time rates among women and a pronounced and gendered part-time culture, as compared to other European countries (EIGE 2014; Barbieri et al 2019;Padavic et al 2019;Plantenga & Remery 2010). This stands in stark contrast to countries with stronger norms of gender equality (such as Sweden, Denmark or Norway), where change has been driven predominantly by men's work adjustments (Nylin et al 2021;Dunatchik & Özcan 2020;Kvande & Brandth 2019).…”
Section: Gendered Inequalities In the Case Of Austriamentioning
confidence: 81%
See 1 more Smart Citation
“…Even though the gap between women's and men's employment in general has decreased in Austria and women indeed increasingly participate in the labor market (Schmidt et al 2020), this country is characterized by high and growing part-time rates among women and a pronounced and gendered part-time culture, as compared to other European countries (EIGE 2014; Barbieri et al 2019;Padavic et al 2019;Plantenga & Remery 2010). This stands in stark contrast to countries with stronger norms of gender equality (such as Sweden, Denmark or Norway), where change has been driven predominantly by men's work adjustments (Nylin et al 2021;Dunatchik & Özcan 2020;Kvande & Brandth 2019).…”
Section: Gendered Inequalities In the Case Of Austriamentioning
confidence: 81%
“…The constructions implied that ideally, women with children have to be supported by a variety of increased imaginable working time and working place options, by models such as part-time leadership, by institutional care or nannies. They would not need support from their male partners who may also take parental leave and reduce or flexibly adjust their working hours to take over childcare responsibilities -one crucial measure towards more gender equality in the division of paid and unpaid labor (Nylin et al 2021;Dunatchik & Özcan 2020). This also has consequences for gender relations in parental couples, between parental partners, regarding their division of paid and unpaid work.…”
Section: Discussionmentioning
confidence: 99%
“…Nylin et al. (2021) showed that mothers’ earnings share declined somewhat less over time among couples having children from 1987 to 2007 in the Swedish registers, and Bergsvik et al. (2020) reported similar findings for the years 2005–2014 based on Norwegian registers.…”
Section: Introductionmentioning
confidence: 88%
“…2020; Lundberg and Rose 2000; Musick, Bea, and Gonalons‐Pons 2020; Nylin et al. 2021). U.S. fixed effect estimates from the Panel Study of Income Dynamics (PSID) show that wives’ relative earnings drop 8 percentage points in the year after first birth in the 1990s and 2000s (Musick, Bea, and Gonalons‐Pons 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation